Analisis Kualitas Layanan Ekspedisi Shopee Express Menggunakan Metode SERVQUAL, IPA, dan PGCV - Wahyudi, M Rafi Rizqi; Andini, Wanda Oktiva; Triyanto, Galih Budhi; Yuliawati, Evi (Metode : Jurnal Teknik Industri, 2025)
The growth of e-commerce in Indonesia has driven an increase in demand for fast, reliable, and high-quality shipping services. One shipping service that has grown rapidly in the digital ecosystem is Shopee Express. As public expectations for the reliability of delivery services continue to rise, various customer complaints still indicate a gap between expectations and reality. The objective of this study is to analyze the quality of service and customer expectations toward Shopee Express using the SERVQUAL approach, Importance Performance Analysis (IPA), and Potential Gain in Customer Value (PGCV). The method used is a quantitative approach with a questionnaire distributed to 60 respondents. The analysis results show that 16 out of 18 service attributes have negative gap values, indicating that service performance has not met customer expectations. Five attributes identified in Quadrant I of IPA are prioritized for improvement. The packaging security attribute (SI2) is the primary focus due to its highest PGCV value. This study concludes that the combination of the three methods can systematically identify the weaknesses in the quality of Shopee Express delivery services. It is hoped that Shopee Express will pay more attention to the key indicators analyzed, thereby improving service quality and enhancing customer satisfaction.